Molecular Beam Epitaxy (MBE) Growth of Model Cathodes to Study Interfacial Ion Diffusion. Issue 30 (13th September 2022) - KC, Bilash; Guo, Jinglong; Farrell, Jack; Nolis, Gene M.; Buchholz, D. Bruce; Evmenenko, Guennadi; Cabana, Jordi; Crabtree, George W.; Klie, Robert F.
Abstract: Lithium‐ion batteries (LIBs) have been the focus of research for decades owing to their superior energy storage potential and wide range of applications. However, long‐term stability issues still persist in LIB cathodes as the result of the formation of a solid electrolyte interface (SEI), structural transformations, or the loss of active cathode materials. In nanoscale cathodes, it is often impossible to isolate, let alone mitigate the causes of the observed capacity loss. Herein, a novel approach is presented to synthesizing LIB cathode model systems using thin‐film molecular beam epitaxy (MBE). Specifically, 100 nm thick LiMn2 O4 (LMO) thin‐film cathodes are grown on SrRuO3 /SrTiO3 (100) single‐crystal substrates and characterized in their pristine and cycled states. The pristine thin films exhibit the electro‐chemical cycling behavior and structural evolution previously seen in bulk LMO cathodes. The formation of surface‐layer rocksalt MnO and spinel Mn3 O4 along with the mass‐loss associated with the corrosion of active Mn ions is also reported.  It is, therefore, demonstrated that these MBE‐grown model systems can be used for detailed studies of their surface structures and the electrode/electrolyte interfacial evolution in LIB cathodes, leading to the development of materials for rechargeable batteries with higher capacity and better stability. Abstract : Molecular‐beam epitaxial (MBE) synthesis of Lithium transition metal oxide thin films is demonstrated using SrTiO3 substrates. Specifically, 100 nm thick single‐crystal LiMn2 O4 films are grown in two different orientations and exhibit surface orientation dependent electro‐chemical cycling properties. Using high‐resolution scanning transmission electron microscopy, the viability of MBE‐grown Li‐oxide films as model Li‐ion battery cathodes is established.